Estudo do envolvimento da neurotransmissão CRFérgica do Núcleo Leito da Estria Terminal (NLET) nas respostas autonômicas desencadeadas pelo estresse por restrição agudo em ratos - Oliveira, Leandro Augusto de (Universidade Federal de São Carlos, 2015)
The corticotropin-releasing factor (CRF) is involved in behavioral and physiological responses to emotional stress through its action in several limbic structures, including the bed nucleus of the stria terminalis (BNST). Nevertheless, the role of CRF1 and CRF2 receptors in the BNST in autonomic adjustments during aversive threat is unknown. Therefore, in the present study we investigated the involvement of CRF receptors within the BNST in autonomic responses evoked by the acute restraint stress in rats. For this, we evaluated the effects of bilateral treatment of the BNST with selective agonists and antagonists of either CRF1 or CRF2 receptors in the arterial pressure and heart rate increase and the decrease in tail skin temperature induced by restraint stress. Microinjection of the selective CRF1 receptor antagonist CP376395 into the BNST reduced the pressor and tachycardiac responses caused by restraint. Conversely, BNST treatment with the selective CRF1 receptor agonist CRF increased restraint-evoked arterial pressure and HR responses and reduced the fall in tail skin temperature response. All effects of CRF were inhibited by local BNST pretreatment with CP376395. The selective CRF2 receptor antagonist antisauvagine-30 reduced the arterial pressure increase and the fall in tail skin temperature. The selective CRF2 receptor agonist urocortin-3 increased restraint-evoked pressor and tachycardiac responses and reduced the drop in cutaneous temperature. All effects of urocortin-3 were abolished by local BNST pretreatment with antisauvagine-30. These findings indicate an involvement of both CRF1 and CRF2 receptors in the BNST in autonomic adjustments during emotional stress.
Keywords: Neuropeptídeos; CRF; Urocortina; NLET; Amigdala extendida; Cardiovascular; Estresse; Neuropeptides; Urocortin; BNST; Extended amygdala; Stress; CIENCIAS BIOLOGICAS::FISIOLOGIA